Substrate temperature effect on the formation of PtRhOx thin films - Lee, K; Lee, KH; Ju, BK (KOREAN PHYSICAL SOC, 2002)
Conductive PtRhOx thin films were deposited at various substrate temperatures on bare Si wafers by means of the reactive sputtering method, using a Pt9Rh alloy target. (111)-axis oriented PtRhOx thin films were obtained for a substrate temperature around 400 degreesC. From the. X-ray photoelectron spectroscopy studies, the atomic ratio of oxygen to platinum, O/Pt, in PtRhOx was found to decrease from 2.3 to 1.5 with increasing substrate temperature from 50 degreesC to 550 degreesC whereas the atomic ratio of Rh to Pt, Rh/Pt, remained constant at about 0.12. These results were attributed to a decrease of in the number of PtO2 binding states, accompanied by an increase in the number of PtO binding states, with the number of Rh2O3 binding states remaining constant. The resistivity of PtRhOx thin films deposited on Si wafers decreased to about 8.9x10(-5) Omegacm with increasing substrate temperature up to 650 degreesC.
Keywords: DENSITY FERROELECTRIC MEMORIES; ELECTRODE-BARRIER; AMMONIA